Scent and the cinema - Spence, C (SAGE Publications, 2020)
From the very earliest days of public cinema (moving pictures), there has been consideration about how odors and scents might influence the viewer’s experience. While initially this was primarily a concern with how to eliminate the malodor of the cinema-goers themselves, in more recent times, there have been a number of well-publicized attempts to add synchronized pleasant (and, on occasion, also unpleasant) scents to “enhance” the cinema experience. While early solutions such as AromaRama and Smell-O-Vision were beset by technical challenges, low-tech scratch and sniff (Odorama) and, more recently, Edible Cinema-type solutions (where the audience get to consume flavourful, and often aromatic, morsels in time with the events on screen) have proved somewhat more successful. Nevertheless, there are a number of key psychological factors that will likely inhibit the uptake of scented cinema in the future, even should the technical and financial issues (associated with retrofitting cinemas, and providing the appropriate fragrances) one day be satisfactorily resolved. These include the phenomenon of “inattentional anosmia” as well as the “fundamental misattribution error,” whereby people (who are, by-and-large, visually-dominant) tend to attribute their enjoyment to the action seen on screen, rather than to smell, and hence are unlikely to pay a premium for the latter.